소나무 임분에서의 트랙터윈치를 이용한 집재작업 생산성 및 비용분석 - 정응진; Eung-jin Jeong; 조민재; Min-jae Cho; 박정묵; Jeong-mook Park; 조구현; Koo-hyun Cho; 유영민; Young-min Yoo; 차두송; Du-song Cha (한국산림과학회지, 2019)
본 연구는 임목수확작업에 사용되는 트랙터윈치의 작업효율성을 검토하기 위하여 강원도 양양군지역의 소나무 간벌지를 대상으로 트랙터윈치를 이용한 전목 집재작업에서의 작업생산성 및 작업비용을 분석하였다. 평균집재거리는 29m, 평균 임목재적은 0.15㎥으로 총 95회 집재작업 중 상향집재가 51%, 하향집재가 49%로 작업이 실행되었다. 집재작업 생산성은 하향집재 2.28㎥/hr, 상향집재 1.89㎥/hr으로 운용적 작업지연시간을 최소화하여 기계이용률을 80%로 높일 경우, 약0.5㎥/hr 생산성이 향상될 것으로 판단된다. 집재작업비용은 하향집재 작업비용(44,116원/㎥)이 집재본수(본/cycle)의 차이로 인하여 상향집재작업비용(53,369원/㎥) 보다 낮게 산출되었다. 또한 상·하향 집재작업시간 예측모델식을 개발하여, 민감도 분석을 실시한 결과, 집재거리(m), 집재본수(본/cycle), 집재경사(%) 순으로 집재작업시간에 영향을 미치는 것으로 분석되었다. 향후 집재방향에 따른 정확한 예측모델식을 개발하기 위하여 추가적인 조사가 필요할 것으로 사료된다. The present study analyzed the productivity and cost of winching operations for evaluating the efficiency of a tractor-attached winch in a Pinus densiflora thinning site located in the Yangyang County of Gangwon-do. The mean yarding distance and mean timber volume were 29 m and 0.15 ㎥, respectively. In the 95 cycles of yarding operations, the uphill and downhill yarding operations constituted 51% and 49%, respectively, of the total yarding operations. The productivity of the uphill yarding operation was 2.28 ㎥/h, and the productivity of the downhill yarding operation was 1.89 ㎥/h. The findings of this study revealedthat productivity would increase by 0.5 ㎥/h when the rate of utilization of the machine is increased to 80% by reducing the operational delay time. The cost of the downhill yarding operation was 44,116 KRW/㎥, whereas that of the uphill yarding operation was 53,369 KRW/㎥. The difference in cost resulted from the difference in the number of yarding stems (stems/cycle). Furthermore, the results of the multiple linear regression equation developed for predicting the yarding operation times showed that productivity was significantly affected by working conditions such as yarding distance (m), the number of stems per cycle (stems/cycle), and the terrain slope (%) in the uphill and downhill yarding operations. Further research is required for developing an accurate prediction model equation according to a yarding direction.